STIPS : a framework for electronic commerce - Tan, Jimmy Puay Hong. (2008)
With the enhancements in Web technology, Electronic Commerce evolved as one of the most promising applications. In this project, we propose an Internet-based shopping model. Three entities are modeled : the customer, the supplier and the middleware. The latter consists of a CORBA interface based on Java that allows two or more distributed object-oriented applications on the Internet to interact with each other.